1987
DOI: 10.1111/j.1558-5646.1987.tb05875.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dispersal Barrier in the Tropical Pacific: Implications for Molluscan Speciation and Extinction

Abstract: Abstract. -Stretches ofdeep ocean constitute barriers to the dispersal ofmany shallow-water marine species in the tropical Pacific. The purpose ofthis study was to assess the selectivity ofthese barriers with respect to the habitat characteristics, adult size, and predation-related shell architecture of gastropods, and to explore the implications of this selectivity for macroevolutionary patterns of extinction and speciation. The dispersal barrier between continental islands (represented in my collections by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 47 publications
(50 reference statements)
0
59
0
2
Order By: Relevance
“…Geographic ranges of species and higher taxa vary through space and time in response to environmental perturbations, local biological interactions, and the formation and destruction of physical barriers to dispersal [1]–[4]. Geographic range is an important attribute of taxa because the durations of many marine organisms in the fossil record are positively correlated with geographic range [5]–[13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geographic ranges of species and higher taxa vary through space and time in response to environmental perturbations, local biological interactions, and the formation and destruction of physical barriers to dispersal [1]–[4]. Geographic range is an important attribute of taxa because the durations of many marine organisms in the fossil record are positively correlated with geographic range [5]–[13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the advantage of studying time-averaged geographic ranges is that high frequency variations (e.g., seasonal, decadal) in areal extent are averaged out [21]. The time dimension of the fossil record, of course, allows geographic ranges to be incorporated into macroevolutionary theory (e.g., [1], [5]–[7], [10], [13], [15], [22]). …”
Section: Introductionmentioning
confidence: 99%
“…A number of taxa in various families have widespread ranges of distribution coupled with genetic homogeneity (Randall 1998; McMillan et al 1999; Planes and Fauvelot 2002; Horne et al 2008). (2) Besides the permanent hard continental barriers that have led to separation between ocean basins (e.g., the rise of the Isthmus of Panama between the Atlantic and Pacific Oceans, Lessios 2008), only a few barriers to coral reef fish dispersal such as oceanic currents (Lessios et al 1999; Barber et al 2000), open‐ocean distances (Vermeij 1987; Lessios and Robertson 2006), and freshwater outflows (Rocha 2004; Floeter et al 2008; Beldade et al 2009) have been identified as important factors in marine speciation (but see Connolly et al 2003 for critical assessment). (3) Barriers that are currently recognized have changed over time.…”
mentioning
confidence: 99%
“…According to classical genetic theory, a marine species with high pelagic dispersal potential is expected to have no clear genetic structure at least below the minimum dispersal distance of individuals [95]–[98] and previous phylogeographic studies on P. noctiluca confirmed this expectation. Indeed, Miller et al [15], in a phylogeographic study performed using mitochondrial cytochrome oxidase subunit I (COI) and two nuclear internal transcribed spacers (ITS1 and ITS2) genes, found high and statistically significant genetic differences (at two out of three markers: COI: Ί ST  = 0.72, P<0.001; ITS2: Ί ST  = 0.023, P<0.001) only between Southern and Northern Atlantic samples, geographically very far from each other (≈10.000 km), whereas no genetic difference was found at a smaller geographic scale.…”
Section: Discussionmentioning
confidence: 99%